Treosulfan compared with reduced‐intensity busulfan improves allogeneic hematopoietic cell transplantation outcomes of older acute myeloid leukemia and myelodysplastic syndrome patients: Final analysis of a prospective randomized trial. Issue 8 (8th June 2022) - Beelen, Dietrich W.; Stelljes, Matthias; Reményi, Péter; Wagner‐Drouet, Eva‐Maria; Dreger, Peter; Bethge, Wolfgang; Ciceri, Fabio; Stölzel, Friedrich; Junghanß, Christian; Labussiere‐Wallet, Hélène; Schaefer‐Eckart, Kerstin; Grigoleit, Goetz U.; et al.
Abstract: The phase III study was designed to compare event‐free survival (EFS) after treosulfan‐based conditioning with a widely applied reduced‐intensity conditioning (RIC) busulfan regimen in older or comorbid patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) undergoing allogeneic hematopoietic cell transplantation (HCT). A previously reported confirmatory interim analysis of the randomized clinical study including 476 patients demonstrated statistically significant noninferiority for treosulfan with clinically meaningful improvement in EFS. Here, the final study results and pre‐specified subgroup analyses of all 570 randomized patients with completed longer‐term follow‐up are presented. Patients presenting HCT‐specific comorbidity index >2 or aged ≥50 years were randomly assigned (1:1) to intravenous (IV) fludarabine with either treosulfan (30 g/m 2 IV) or busulfan (6.4 mg/kg IV) after stratification by disease risk group, donor type, and participating institution. The primary endpoint was EFS with disease recurrence, graft failure, or death from any cause as events. EFS of patients (median age 60 years) was superior after treosulfan compared to RIC busulfan: 36‐months‐EFS rate 59.5% (95% CI, 52.2–66.1) vs. 49.7% (95% CI, 43.3–55.7) with a hazard ratio (HR) of 0.64 (95% CI, 0.49–0.84), p = 0.0006. Likewise, overall survival (OS) with treosulfan was superior compared to busulfan: 36‐month‐OS rate 66.8% vs. 56.3%; HR 0.64 (95% CI, 0.48–0.87), p = 0.0037. Post hoc analyses revealed that these differences were consistent with the confirmatory interim analysis, and thereby the treosulfan regimen appears particularly suitable for older AML and MDS patients.